Magnetic Resonance Imaging Findings of the Proximal Metacarpal Region in Warmblood Horses: 36 Lame and 26 Control Limbs (2015–2021) - van Veggel, Elisabeth; Selberg, Kurt; van der Velde-Hoogelander, Brenda; Bolas, Nick; Vanderperren, Katrien; Bergman, Hendrik Jan (Frontiers in Veterinary Science, 2021)
Objectives: To evaluate the distribution and severity of bone and soft tissue lesions in the proximal metacarpal region of Warmblood horses in lame and control groups. Correlation between lesions and ability to return to work was evaluated in the lame group. Methods: Retrospective analysis of 62 horses with MRI examination of the proximal metacarpal region between Sept 2015 and Feb 2021. There were 36 lame limbs and 26 control limbs. The control group included 7 contralateral limbs. Results: Proximal suspensory ligament (PSL) size was not different between the lame and control groups. Hyperintensity seen on T1/T2*W GRE images within the dorsal collagenous part of the PSL, hyperintense Short-TI Inversion Recovery (STIR) signal within the dorsal collagenous part of the PSL or within the McIII were only present within the lame group. Palmar cortical McIII resorption, dorsal margin irregularity of the PSL and McIII sclerosis were more severe within the lame limbs, but mild gradations were also seen in control limbs. Intermediate gradings for a subset of lesions were commonly seen in the non-lame contralateral to lame limbs. Return to work in the lame group is not statistically different for any measured observation(s) and 19/33 of the lame horses returned to work at similar or higher levels. Conclusion and clinical importance: 58% in this group of Warmblood horses returned to work within a variable time frame. The majority (81%) of lame limbs showed bone and soft tissue abnormalities, but no enlargement of the PLS was noted in lame horses, and no correlation was seen between the severity or type of lesions and the ability to return to work. The presence of STIR hyperintensity within the proximal McIII or dorsal collagenous part of the PSL, hyperintensity within the dorsal collagenous part of the PSL on T1W GRE and T2*W GRE images as well as significant palmar cortical McIII resorption are considered clinically relevant lesions. Contralateral limbs may not truly represent the normal condition, showing non-clinical variations and adaptive remodelling.